2016
DOI: 10.1371/journal.pone.0159414
|View full text |Cite
|
Sign up to set email alerts
|

Combined Iron Chelator and Antioxidant Exerted Greater Efficacy on Cardioprotection Than Monotherapy in Iron-Overloaded Rats

Abstract: BackgroundIron chelators are used to treat iron overload cardiomyopathy patients. However, a direct comparison of the benefits of three common iron chelators (deferoxamine (DFO), deferiprone (DFP) and deferasirox (DFX)) or an antioxidant (N-acetyl cysteine (NAC)) with a combined DFP and NAC treatments on left ventricular (LV) function with iron overload has not been investigated.Methods and FindingsMale Wistar rats were fed with either a normal diet or a high iron diet (HFe group) for 4 months. After 2 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 66 publications
(108 reference statements)
3
44
1
Order By: Relevance
“…Although iron overload did not alter the level of cardiac LTCC protein in this study, LTCC activity might be altered in the hearts of the HFe-fed rats and this needs to be investigated further. In addition, our previous study found that rats with iron-overload for 4 months had both increased systemic iron (plasma NTBI) and cardiac iron concentrations42 which were consistent with an increase in TTCC protein expression in this study. Plasma NTBI levels were used to determine an iron status in iron-overloaded patients including hereditary hemochromatosis, β-thalassemia, myelodysplastic syndrome and sickle cell disease51.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although iron overload did not alter the level of cardiac LTCC protein in this study, LTCC activity might be altered in the hearts of the HFe-fed rats and this needs to be investigated further. In addition, our previous study found that rats with iron-overload for 4 months had both increased systemic iron (plasma NTBI) and cardiac iron concentrations42 which were consistent with an increase in TTCC protein expression in this study. Plasma NTBI levels were used to determine an iron status in iron-overloaded patients including hereditary hemochromatosis, β-thalassemia, myelodysplastic syndrome and sickle cell disease51.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, %LVEF was significantly decreased in the HFe-fed rats leading to LV dysfunction in our study. In addition, our previous study and others demonstrated that an increase in cardiac iron store led to increased cardiac oxidative stress which caused increased mitochondrial dysfunction, resulting in cardiac dysfunction and iron overload cardiomyopathy742. In consistency, a previous study found that iron overload-evoked production of cardiac oxidative stress contributed to damage to mitochondrial DNA, reduced complex I (NADH dehydrogenase) and complex IV (cytochrome c oxidase) activities, and decreased cardiac mitochondrial respiration, leading to mitochondrial and cardiac dysfunctions in iron-overloaded mice56.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Importantly, the protective role of NAC in BPA toxicity has recently been revealed in a rat model of BPA‐induced neurotoxicity . Furthermore, there are increasing research data supporting the advantage of NAC as an effective mitochondrial protective agent apart from its antioxidant potential . As oxidative stress and mitochondrial alterations are the hallmark of the pathogenesis in both AKI and BPA, we therefore examined the possible protection by NAC against any impacts of BPA in the kidneys after ischemia–reperfusion episode.…”
Section: Introductionmentioning
confidence: 99%